Diversity and cultural significance of medicinal plants among multiethnic communities in Jambi Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Asra R, Maryani AT, Yelianti U, Fijridiyanto IA, Adriadi A, Wibowo CAP, Saputri VA, Febrianti A. 2025. Diversity and cultural significance of medicinal plants among multiethnic communities in Jambi Province, Indonesia. Biodiversitas 26: 5023-5039. This study aims to document local knowledge of medicinal plants, analyze species diversity, plant parts used, processing methods, as well as cultivation and conservation practices among three major ethnic communities in Jambi Province, Indonesia: Javanese, Kerinci, and Malay. Data were collected through field observations, documentation, and in-depth interviews with more than 75 informants selected using purposive and snowball sampling techniques. Both qualitative and quantitative analyses were employed, using the Cultural Significance Index (CSI) and Plant Part Value (PPV), with CSI statistical significance thresholds applied to distinguish cultural importance across species. A total of 156 species belonging to 61 families were recorded, with Zingiberaceae being the most dominant. Leaves were the most frequently used plant part (49.75%). The highest CSI value was recorded for Allium sativum (60), while the lowest (3) was found in Saraca indica, Styrax benzoin, and Salvia rosmarinus. In terms of disease categories, medicinal plants were most commonly used for diabetes (16.67%), followed by fever (13.46%) and hypertension (12.18%). Knowledge transmission was largely ancestral (62%), supplemented by personal experience (21%), social interactions (10%), and modern sources (7%). These findings highlight the enduring role of medicinal plants as both a health resource and cultural heritage. This study represents the first comparative ethnobotanical analysis of Javanese, Kerinci, and Malay communities in Jambi, contributing novel insights into biodiversity documentation and conservation strategies rooted in local wisdom.
Keywords: Ethnobotany, Jambi, Javanese, Kerinci, Malay